Broad and Fine Scale Variability in Bacterial Diversity and Cyanotoxin Quotas in Benthic Cyanobacterial Mats - Thomson-Laing, Georgia; Puddick, Jonathan; Laroche, Olivier; Fulton, Samantha; Steiner, Konstanze; Heath, Mark W.; Wood, Susanna A. (Frontiers in Microbiology, 2020)
Benthic proliferations of Microcoleus autumnalis (basionym Phormidium autumnale) and closely related taxa are being reported with increasing frequency in streams and rivers worldwide. This species commonly produces the potent neurotoxin anatoxin, and exposure to this has resulted in animal fatalities and human health concerns. Bacterial communities within cyanobacterial assemblages can facilitate processes such as nutrient cycling and are posited to influence cyanobacterial growth and function. However, there is limited knowledge on spatial variability of bacterial communities associated with benthic cyanobacteria and anatoxin content and quotas. In this study, M. autumnalis-dominated mat samples were collected from six sites in two New Zealand streams. Associated bacterial communities were characterized using 16S rRNA metabarcoding, anatoxin content by liquid chromatography-mass spectrometry and anaC copies using droplet digital PCR. Bacterial assemblages differed significantly when amplicon sequence variants were compared between streams and most sites within streams. These differences were associated with conductivity, DRP, DIN, temperature, anatoxin concentration and quota. Despite the differences in bacterial community composition; at phyla, class and order levels there was high similarity across spatial scales, with Bacteroidetes (ca. 67%) and Proteobacteria (ca. 25%) dominant. There was significant variability in total anatoxin concentrations between sites in both streams (p < 0.001). When the data were converted to anatoxin quotas variability was reduced, suggesting that the relative abundance of toxic genotypes is a key driver of total anatoxin concentrations in mats. This study demonstrates the complexity of microbial communities within M. autumnalis-dominated mats and highlights their likely important role in within-mat nutrient cycling processes.